Ideološke premise ameriškega pravnega realizma - Spruk, Jure (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2024)
The author discusses American legal realism and its ideological traits. From a legal-theoretical standpoint, American legal realism can be understood as a theory of judicial decision- making that developed especially in the 1920s and 1930s in response to Langdell’s formalism and formalistic judicial decision-making. Instead of focusing on legal rules, American legal realists focused on the facts of concrete cases. They were less interested in the internal logic of legal reasoning and more concerned with its consequences. The social contextualisation of the main theoretical premises of American legal realism reveals their ideological implications. From an ideological perspective, the critique of legal formalism signified a critique of classical liberal ideological constructs - particularly the notion of a neutral and free market - which concentrated social power in the hands of individuals and corporations at the expense of less privileged social groups. The critique of the exact calculations of the correctness of judicial decision-making was, in effect, a critique of the notion of a naturally inevitable market as a fair mediator between the interests of materially unequal individuals and social groups.
Keywords: American legal realism; ameriški pravni realizem; ideologija; ideology; teorija prava; theory of law; ZDA